Effect of cigarette smoke on monocyte procoagulant activity: Focus on platelet-derived brain-derived neurotrophic factor (BDNF). (2nd January 2017) - Amadio, Patrizia; Baldassarre, Damiano; Sandrini, Leonardo; Weksler, Babette B.; Tremoli, Elena; Barbieri, Silvia S.
Abstract: Cigarette smoke (CS) activates platelets, promotes vascular dysfunction, and enhances Tissue Factor (TF) expression in blood monocytes favoring pro-thrombotic states. Brain-derived neurotrophic factor (BDNF), a member of the family of neurotrophins involved in survival, growth, and maturation of neurons, is released by activated platelets (APLTs) and plays a role in the cardiovascular system. The effect of CS on circulating levels of BDNF is controversial and the function of circulating BDNF in atherothrombosis is not fully understood. Here, we have shown that human platelets, treated with an aqueous extract of CS (CSE), released BDNF in a dose-dependent manner. In addition, incubation of human monocytes with BDNF or with the supernatant of platelets activated with CSE increased TF activity by a Tropomyosin receptor kinase B (TrkB)-dependent mechanism. Finally, comparing serum and plasma samples of 12 male never smokers (NS) and 29 male active smokers (AS) we observed a significant increase in microparticle-associated TF activity (MP-TF) as well as BDNF in AS, while in serum, BDNF behaved oppositely. Taken together these findings suggest that platelet-derived BDNF is involved in the regulation of TF activity and that CS plays a role in this pathway by favoring a pro-atherothrombotic state.